The role of ICTs in creating the new social public place of the digital era - Ayat Ayman Abdel-Aziz; Hassan Abdel-Salam; Zeyad El-Sayad (Alexandria Engineering Journal, 2016)
Nowadays, Information and Communication Technologies (ICTs) have spread extensively in everyday life in an unprecedented way. A great attention is paid to the ICTs while ignoring the social aspect. With the immersive invasion of internet as well as smartphones’ applications and digital social networking, people become more socially connected through virtual spaces instead of meeting in physical public spaces. ICTs are categorized in this paper into four elements which are as follows: Wi-Fi networks, digital interactive media façades, interactive public displays, and smartphones’ applications in public spaces. These elements will play major roles in the public space classified into five domains which are as follows: culture and art, education, planning and design, games and entertainment, and information and communication. Based on this classification various examples and proposals of ICTs interventions in public spaces are presented to encourage good old fashioned social interaction by creating the new social public place of this digital era. Accordingly, this study will help to find design principles that can be adopted in the design of future public spaces to meet the needs of the digital era’s users with the new concepts of social life respecting the rules of place-making.